PTH-145 Comparison Of Percutaneous Endoscopic Gastrostomy, Megestrol Acetate And Nasogastric Feeding In Patients With Cystic Fibrosis. (9th June 2014) - Shabbir, S; Zaidi, M; Mughal, L; Bright-Thomas, RJ; Jones, RB
Abstract : Introduction: Malnutrition remains an important and common problem in cystic fibrosis (CF) patients and weight loss associated with poor lung function is considered a predictor of mortality, although weight loss has also been found to be an independent predictor of mortality 1, 2 . Our aim was to compare changes in weight and FEV1 in CF patients receiving one of 3 interventions to prevent weight loss at 6 and 12 months: i) Percutaneous Endoscopic Gastrostomy (PEG), ii) oral steroid therapy (megestrol acetate- MA) or iii) nasogastric (NG) tube feeding. Methods: We retrospectively collected data from hospital record of patients attending the Manchester Adult Cystic Fibrosis Centre (MACFC) between June 1998 and June 2012 including all living patients on any of the interventions. Results: 53 patients fulfilled criteria at 6 months: 18 MA, 14 NG and 21 PEG. There were significant increases in weight from post-intervention time 0 for MA (mean 3.0 kg, 95% CI: 1.16, 4.85) and NG (mean 2.9 kg, 95% CI: 0.84, 4.97), but not for PEG (mean 1.0 kg, 95% CI: ‑0.64, 2.73). There were no significant changes in FEV1 from time 0 for any of the 3interventions at 6 months; although the ratio of change in FEV1 (6 months:time 0) showed small reductions for all 3 interventions; MA (ratio 0.987, 95% CI: 0.882, 1.104), NG (ratio 0.996, 95% CI: 0.876, 1.133) and PEG (ratio 0.925, 95% CI: 0.836, 1.024). 50 patients fulfilled criteria at 12 months: 16 MA, 13 NG and 21 PEG. There were significant increases in weight from time 0 for MA(mean 2.6 kg, 95% CI: 0.38, 4.78), NG (mean 3.2 kg, 95% CI: 0.73, 5.67) and PEG (mean 2.5 kg, 95% CI: 0.60, 4.46). There were no significant changes in FEV1 over 12 months for any of the 3 interventions although the ratio of change in FEV1 (12 months:time 0) showed small changes for MA (ratio 1.030, 95% CI: 0.923, 1.150), NG (ratio 0.957, 95% CI: 0.840, 1.092) and PEG (ratio 1.041, 95% CI: 0.944, 1.147). Conclusion: All 3 interventions appear to be equally effective means of improving nutritional status as measured by weight gain, and possibly stabilise lung function. Our study is the first which to compare these 3 different interventions but is limited by the small sample size and lack of a control group. Robust prospective studies comparing interventions to improve nutritional status in these patients are required. References: Van Biervliet S, De Waele K, Van Winckel M, Robberecht E. Percutaneous endoscopic gastrostomy in cystic fibrosis: patient acceptance and effect of overnight tube feeding on nutritional status. Acta Gastroenterol Belg 2004 Jul-Sep;67(3):241–4 Sharma R, Florea VG, Bolger AP, Doehner W, et al . Wasting as an independent predictor of mortality in patients with cystic fibrosis. Thorax 2001:56:746–750 Disclosure of Interest: None Declared.